2000
DOI: 10.1021/ja0014537
|View full text |Cite
|
Sign up to set email alerts
|

Nonstoichiometric La2-xGeO5-δ Monoclinic Oxide as a New Fast Oxide Ion Conductor

Abstract: Oxide ion conductivity in La(2)GeO(5)-based oxide was investigated and it was found that La-deficient La(2)GeO(5) exhibits oxide ion conductivity over a wide range of oxygen partial pressure. The crystal structure of La(2)GeO(5) was estimated to be monoclinic with P2(1)/c space group. Conductivity increased with increasing the amount of La deficiency and the maximum value was attained at x = 0.39 in La(2 - x)GeO(5 - delta). The oxide ion transport number in La(2)GeO(5)-based oxide was estimated to be unity by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 14 publications
2
38
0
Order By: Relevance
“…High values of the conductivity have been also reported for La 9.66 Ge 6 O 30Àd with s ¼ 0:199 S cm À1 at 9501C. However, a monoclinic structure was reported for this compound (14).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…High values of the conductivity have been also reported for La 9.66 Ge 6 O 30Àd with s ¼ 0:199 S cm À1 at 9501C. However, a monoclinic structure was reported for this compound (14).…”
Section: Introductionmentioning
confidence: 75%
“…However, such a comparison is only possible with Gd 2 GeO 5 as Dy 2 GeO 5 crystallizes in a different space group (I2=a), the a-axis parameter reported for Eu 2 GeO 5 is too large and not in agreement with the powder data reported in the JCPDS (21) and the calculated positions for the oxygen ions in La 2 GeO 5 and Nd 2 GeO 5 result in very distorted GeO 4 tetrahedra. In the work by Ishihara et al (14), the authors claimed to have prepared La-deficient samples with composition La 2Àx GeO 5Àd and with a monoclinic structure for values of xr0:45: However, their structural data reveal that the change in the unit cell parameters is not significant although a large decrease would be expected by such an La and O ion deficiency. Furthermore, their structural models reveal very distorted GeO 4 tetrahedra.…”
Section: La 2 (Geo 4 )Omentioning
confidence: 99%
“…Recently high oxide ion conductivity has been reported in the oxide apatitetype system Ln10.ySi6026_+ z (Ln = rare earths) as well as AI doped variants, with conductivities higher than YSZ at intermediate temperatures (4.3 • 10 .3 S-cm -~ vs. 1 • 10 .3 S-cm -~ at 500 ~ [1][2][3][4][5]. Arikawa et al have subsequently reported that the Ge analogue La~oGe60 z and in particular the Sr doped version LagSrtGe60 ~ exhibit even higher conductivity [6], although the exact nature of the conducting phase in this latter system is still the subject of discussion, with the same authors subsequently claiming that it was cation deficient La2GeO5 type [7]. The reason for this confusion appears to be due to the fact that loss of Ge occurs at high temperatures leading to a trans-"Corresp.…”
Section: Introductionmentioning
confidence: 99%
“…However, powder diffraction data contains information about disorder and defects in the form of diffuse scattering which is often ignored. The use of real-space pair distribution function (PDF) techniques is becoming increasingly popular in the study of disordered and nanoscale materials [1][2][3]. The PDF has peaks corresponding to inter atomic distances.…”
mentioning
confidence: 99%
“…[ Rare earth oxy-apatites are nowadays interesting due to their high oxide ion conductivities and low activation energies, properties that are making these materials promising electrolytes for solid oxide fuel cells, SOFCs [1]. An attractive system related with the apatite-type phases is the monoclinic La 2-x GeO 5-3x/2 series, synthesized and studied by Ishihara et al [2]. The structural formula of this series is better expressed as La 2-x (GeO 4 )O 1-3x/2 to highlight its oxy-germanate character.…”
mentioning
confidence: 99%